PENGELOLAAN SUPERVISI AKADEMIK SEBAGAI STRATEGI MENINGKATKAN KUALITAS PEMBELAJARAN DI SEKOLAH DASAR - Lastini, Fitri; Sutama, Sutama; Achmad Fatoni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe the implementation of academic supervision at SD Negeri 03 Jatiwarno, focusing on fostering and improving teachers' competencies and developing the learning process. The research employs a phenomenological qualitative approach to explore the phenomenon of academic supervision conducted by the school principal at SD Negeri 03 Jatiwarno, Karanganyar. This method emphasizes a deep understanding of the meaning attributed by subjects to their experiences within the context of academic supervision. Data were collected through observations, interviews, and documentation, then analyzed using triangulation techniques to ensure data validity. The findings indicate that academic supervision consists of three main stages: planning, implementation, and follow-up. Intensive and continuous academic supervision has a positive impact on teachers' performance and the quality of learning, motivating teachers to continually update their knowledge and skills. Effective supervision not only aids teachers in the learning process but also creates a conducive learning environment that supports educational goals.